Effectiveness of women-led community interventions in improving tuberculosis preventive treatment in children: results from a comparative, before–after study in Ethiopia - Jacob Creswell; Degu Jerene; Ahmed Bedru; Dawit Assefa; Kalkidan Tesfaye; Samuel Bayu; Samuel Seid; Fikirte Aberra; Amera Khan (BMJ Open)
Objectives Our objective was to evaluate the impact of a service delivery model led by membership-based associations called Iddirs formed by women on tuberculosis preventive treatment (TPT) initiation and completion rates among children.Design Comparative, before-and-after study design.Setting Three intervention and two control districts in Ethiopia.Participants Children who had a history of close contact with adults with infectious forms of tuberculosis (TB). Child contacts in whom active TB and contraindications to TPT regimens were excluded were considered eligible for TPT.Interventions Between July 2020 and June 2021, trained women Iddir members visited households of index TB patients, screened child household contacts for TB, provided education and information on the benefits of TPT, linked them to the nearby health centre and followed them at home for TPT adherence and side effects. Two control zones received the standard of care, which comprised of facility-based provision of TPT to children. We analysed quarterly TPT data for treatment initiation and completion and compared intervention and control zones before and after the interventions and tested for statistical significance using Poisson regression.Primary and secondary outcome measures There were two primary outcome measures: proportion of eligible children initiated TPT and proportion completed treatment out of those eligible.Results TPT initiation rate among eligible under-15-year-old children (U15C) increased from 28.7% to 63.5% in the intervention zones, while it increased from 34.6% to 43.2% in the control zones, and the difference was statistically significant (p<0.001). TPT initiation rate for U5C increased from 13% (17 out of 131) to 93% (937 out of 1010). Of the U5C initiated, 99% completed treatment; two discontinued due to side effects; three parents refused to continue; and one child was lost to follow-up.Conclusion Women-led Iddirs contributed to significant increase in TPT initiation and completion rates. The model of TPT delivery should be scaled-up.